Effective Teaching Practices in Higher Education during Covid-19 Pandemic: Lecturers and Students’ Lens (NOBEL: Journal of Literature and Language Teaching, 2023)
This article investigates lecturers’ and students’ perspectives on effective teaching practices in Islamic higher education during the Covid -19 pandemic. The pandemic caused the movement of teaching and learning modes from face to face into online/distance teaching and learning. The different modes of teaching and learning processes may raise a different perspective on effective teaching and learning practices, especially in Islamic higher education. Thirteen English lecturers and 262 English students from the third, fifth, and seventh semesters participated in this survey research. Questionnaires are distributed through Google Forms to collect data on lecturers’ and students’ perspectives on effective teaching practices. The results show that the lecturers and students have good perspectives on four aspects of online teaching (pedagogical, managerial, social, and technological roles) as effective teaching practices in higher education during the Covid-19 pandemic. However, lecturers and students have quite different sequences of most frequent responses on the roles. The three sequences of the lecturers’ responses are social roles, managerial roles, and pedagogical roles. Then the three sequences of the students’ responses are pedagogical roles and managerial roles (two positions: the second and third positions). This different perspective can be a consideration in conducting online teaching and learning.